2017
DOI: 10.1007/s10803-017-3252-8
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behaviour Therapy Versus a Counselling Intervention for Anxiety in Young People with High-Functioning Autism Spectrum Disorders: A Pilot Randomised Controlled Trial

Abstract: The use of cognitive-behavioural therapy (CBT) as a treatment for children and adolescents with autism spectrum disorder (ASD) has been explored in a number of trials. Whilst CBT appears superior to no treatment or treatment as usual, few studies have assessed CBT against a control group receiving an alternative therapy. Our randomised controlled trial compared use of CBT against person-centred counselling for anxiety in 36 young people with ASD, ages 12–18. Outcome measures included parent- teacher- and self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…While this body of work suggests that CBT shows moderate effect sizes for co‐occurring anxiety and ASD in youth, there remains considerable heterogeneity in the effects between studies (Kreslins, Robertson, & Melville, ; Reynolds, Wilson, Austin, & Hooper, ; Ung, Selles, Small, & Storch, ), with estimates ranging from large (e.g., Chalfant et al, ) to small (e.g., Sofronoff, Attwood, & Hinton, ), and at least one documented instance of increased anxiety over treatment (as rated by parents, but not clinicians; Ooi et al, ). A Cochrane review further found that while CBT was effective for reducing anxiety diagnoses in youth with ASD when compared with waitlist controls, no differences were found when comparing CBT to active control treatments or treatment as usual (James, James, Cowdrey, Soler, & Choke, ), which aligns with other recent work showing no differences between CBT and person‐centered therapy for youth with co‐occurring ASD and anxiety (Murphy et al, ).…”
Section: Introductionsupporting
confidence: 70%
“…While this body of work suggests that CBT shows moderate effect sizes for co‐occurring anxiety and ASD in youth, there remains considerable heterogeneity in the effects between studies (Kreslins, Robertson, & Melville, ; Reynolds, Wilson, Austin, & Hooper, ; Ung, Selles, Small, & Storch, ), with estimates ranging from large (e.g., Chalfant et al, ) to small (e.g., Sofronoff, Attwood, & Hinton, ), and at least one documented instance of increased anxiety over treatment (as rated by parents, but not clinicians; Ooi et al, ). A Cochrane review further found that while CBT was effective for reducing anxiety diagnoses in youth with ASD when compared with waitlist controls, no differences were found when comparing CBT to active control treatments or treatment as usual (James, James, Cowdrey, Soler, & Choke, ), which aligns with other recent work showing no differences between CBT and person‐centered therapy for youth with co‐occurring ASD and anxiety (Murphy et al, ).…”
Section: Introductionsupporting
confidence: 70%
“…As shown in Table 4, the overall quality of almost all the studies reviewed was “moderate” ( N = 16; 48.5%) or “weak” ( N = 15; 45.5%), with only two studies meeting “strong” global ratings (i.e. McConachie et al, 2014; Murphy et al, 2017). Of the 13 effectiveness studies, 5 studies (39%) were of “moderate” quality and 6 (46%) were of “weak” quality.…”
Section: Resultsmentioning
confidence: 99%
“…Post-implementation, two studies evaluated therapists’ training efforts (Drmic et al, 2017; Reaven et al, 2015), and about half gathered information about the acceptability of the intervention (e.g. satisfaction, attendance, written feedback, treatment completion, interviews; Burke et al, 2017; Drmic et al, 2017; Hepburn et al, 2016; Mackay et al, 2017; McConachie et al, 2014; Murphy et al, 2017; Reaven et al, 2015), often from multiple perspectives (e.g. therapists, parents, teachers, children/youth).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one intervention study has used independent observer ratings of alliance with participants with autism. As part of a pilot randomized-controlled trial (RCT) comparing CBT to non-directive, supportive counselling for adolescents with autism, Murphy and colleagues (2017) used the Therapy Process Observational Coding Scheme–Alliance Scale (TPOCS-A; McLeod & Weisz, 2005) as an index of treatment fidelity. Results indicated good interrater agreement among coders, and independent observer ratings of alliance were comparable to those given in previous therapy studies involving youth without autism (Brown et al, 2015).…”
mentioning
confidence: 99%